Inmates Hacked Way to $225,000 in Credit. - FORTIN, JACEY (New York Times, 2018)
The article reports on the discovery on the hacking of inmates at the Idaho Department of Correction which led to improper credit in their accounts at JPay Inc., a prison financial services provider, on July 2, 2018.